Two new neotropical genera of the shore-fly tribe Ephydrini Zetterstedt (Diptera: Ephydridae) - Mathis, Wayne N. (Zootaxa, 2008)
Two new shore-fly genera, Paraephydra gen. nov. and Neoephydra gen. nov., from the Neotropical Region are described. Paraephydra is revised and includes P. freitasi (Oliveira), comb. nov. and P. stauros, sp. nov. For the genus Neoephydra, N. araucaria, sp. nov., is described and new combinations are made for most Neotropical species previously placed in Dimecoenia. The tribe Ephydrini is characterized and a key to the genera of this tribe is presented.